Construction contracts laws and management - Murdoch, J. R. (E & FN Spon, 1996)
This text covers the law governing construction contracts, and the management and administration of those contracts. Although the legal principles involved are an aspect of the general law of the contract, the practical and commercial complexities of the construction industry have increasingly made it a specialist area. If lawyers need a greater appreciation of the practical issues arising in constructin cases, there is no doubt that construction professionals need to be better informed about the relevant principles of law. This book, although addressed primarily to the latter group, should be of great assitance to both. Those who already have a basic understanding of the principles of contract and tort should find this book useful. It takes them through the issues peculiar to construction contracts, illustrating those issues throughout by reference to a range of standard form contracts used in the industry.